The relationship between Freshman students' mental health and academic achievement: chain mediating effect of learning adaptation and academic self-efficacy - Xiuli Song; Qian Hu (BMC, 2024)
Abstract The relationship between the mental health and academic achievement of college students is not only related to their individual growth and development but also has a profound impact on the quality of higher education and the cultivation of social talent. Understanding the interaction and influencing mechanisms between mental health and academic achievement can help individuals adjust learning and psychological states and achieve a virtuous cycle between mental health and academic achievement. A survey was conducted on 3871 freshmen using the Symptom Check-List-90 (SCL-90), Academic Self-efficacy Scale (ASES), China College Student Adjustment Scale (CCSAS), and basic quality assessment scores. The results showed that (1) Mental health is significantly correlated with learning adaptation, academic self-efficacy, and academic achievement, and mental health can significantly negatively predict academic achievement; (2) Learning adaptation partially mediates the relationship between mental health and academic self-efficacy; Academic self-efficacy plays a complete mediating role between mental health and academic achievement; (3) Learning adaptation and academic self-efficacy play a chain mediated role between mental health and academic achievement. Therefore, schools can enhance the cultivation of students' psychological qualities, cultivate their adaptability to changes in learning environments and learning methods, and systematically enhance the cultivation of students' academic self-efficacy to improve their academic achievements.